2023
DOI: 10.3390/jcm12051765
|View full text |Cite
|
Sign up to set email alerts
|

Simulators and Simulations for Extracorporeal Membrane Oxygenation: An ECMO Scoping Review

Abstract: High-volume extracorporeal membrane oxygenation (ECMO) centers generally have better outcomes than (new) low-volume ECMO centers, most likely achieved by a suitable exposure to ECMO cases. To achieve a higher level of training, simulation-based training (SBT) offers an additional option for education and extended clinical skills. SBT could also help to improve the interdisciplinary team interactions. However, the level of ECMO simulators and/or simulations (ECMO sims) techniques may vary in purpose. We present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…The former have recently been evaluated systematically, which revealed that two different models are currently even evaluated in randomized controlled trials [13 && ]. Models specifically dedicated to ECMO can still be improved in terms of fidelity as shown in a recent review focusing on educational simulation, while their clinical reliability might more be within reach in the years to come [9,11,14,15].…”
Section: Perspectives For Clinical Decision Supportmentioning
confidence: 99%
“…The former have recently been evaluated systematically, which revealed that two different models are currently even evaluated in randomized controlled trials [13 && ]. Models specifically dedicated to ECMO can still be improved in terms of fidelity as shown in a recent review focusing on educational simulation, while their clinical reliability might more be within reach in the years to come [9,11,14,15].…”
Section: Perspectives For Clinical Decision Supportmentioning
confidence: 99%
“…[7][8][9][10] De hecho, la formación y entrenamiento en ECMO, basado en la simulación, está emergiendo como una herramienta fundamental para mejorar las habilidades técnicas. 11 Analizamos nuestra experiencia en la formación médica especializada con cursos de simulación avanzada en el uso y manejo de la ECMO, basados sus conceptos fundamentales en las recomendaciones internacionales. [12][13][14] Revisamos el impacto educativo con nuestras actividades formativas teórico-prácticas.…”
Section: Introductionunclassified
“…The paradigm shift is underway in teaching and ECMO simulation, most evident by the recent development of simulation models and commercial systems that incorporate game-type elements in scenarios based on problem-based learning (trouble shooting) or various training components. 2 These systems or training models have evolved from mechanical low fidelity systems to more decision-based learning by higher fidelity systems. Virtual team building or individual mentoring are also conceivable over long distances to increase patient safety through training.…”
mentioning
confidence: 99%